Decolonising the History of Islam in the “Lands below the Wind”: The Orientalist vis-à-vis Revisionist Theories - Arif, Syamsuddin (IIUM Journal of Religion and Civilisational Studies, 2025)
A debated topic in the history of Southeast Asia revolves around the coming, spread, and influence of Islam in the Malay-Indonesian Archipelago: whether Islam was brought to the region in the 13th century or earlier; whether it came from India or directly from Arabia; whether it was propagated by traders, by itinerant Sufis, or by missionaries; and whether conversion to Islam washed over traditional society but has left its basic way of life intact, or transformed the society and changed its underlying structure and worldview. This article seeks to “decolonise” the historical writing about the arrival and impact of Islam in the Malay world by critically assessing the positions and arguments of the European Orientalists and their opponents, often called “Revisionist” historians, who have presented new data and fresh interpretations in an effort to challenge the dominant view and separate fact from fiction, as well put the matter to rest.